Optometry Students’ Mental Health at a University in South Africa: Investigating the Links Between Anxiety, Depression, and Key Variables - Vagiri R; Sukati V; Mphasha MH; Mayimele N; Bangalee V; Grootboom W; Makhele L; Padayachee N (Clinical Optometry)
Rajesh Vagiri,1 Velibanti Sukati,2 Mabitsela Hezekiel Mphasha,3 Nsovo Mayimele,4 Varsha Bangalee,5 Wandisile Grootboom,6 Letlhogonolo Makhele,7 Neelaveni Padayachee8 1Department of Pharmacy, Faculty of Health Sciences, University of Limpopo, Mankweng, Limpopo, 0727, South Africa; 2Department of Optometry, Faculty of Health Sciences, University of Limpopo, Mankweng, Limpopo, 0727, South Africa; 3Department of Public Health, Faculty of Health Sciences, University of Limpopo, Mankweng, Limpopo, 0727, South Africa; 4Department of Pharmaceutical Sciences, Faculty of Science, Tshwane University of Technology, Pretoria, 0001, South Africa; 5Discipline of Pharmaceutical Sciences, School of Health Sciences, University of Kwazulu-Natal, Durban, KwaZulu-Natal, 4000, South Africa; 6Medical School, Nelson Mandela University, Port Elizabeth, 6031, South Africa; 7School of Pharmacy, Sefako Makgatho Health Sciences University, Molotlegi St., Ga-Rankuwa, Pretoria, 0208, South Africa; 8Department of Pharmacy and Pharmacology, School of Therapeutic Sciences, Faculty of Health Sciences, University of Witwatersrand, Johannesburg, Gauteng, 2193, South AfricaCorrespondence: Rajesh Vagiri, Department of Pharmacy, Faculty of Health Sciences, University of Limpopo, Mankweng, Limpopo, 0727, South Africa, Tel +2715 268 4842, Email rajesh.vagiri@ul.ac.zaIntroduction: Anxiety and depression in optometry students are becoming acknowledged as critical concerns, especially given the rigorous demands of their academic curricula. This study aimed to identify the severity of anxiety and depression and their association with socio-demographic, academic, and clinical variables among optometry students in South Africa.Methods: This study was a descriptive, quantitative, and cross-sectional study involving 171 optometry undergraduate students at a university in South Africa. Data was gathered using the Generalized Anxiety Disorder (GAD-7) scale, the Patient Health Questionnaire (PHQ-9), and a questionnaire encompassing socio-demographic, student, and clinical variables. Students who agreed to participate and provided written consent were recruited to participate in this study. The association between socio-demographic, student, and clinical variables with total GAD-7 and PHQ-9 scores was determined using the Mann–Whitney U-test and Kruskal–Wallis test where applicable.Results: More than half of the participants were female (n=63; 63.2%), identified as belonging to the Pedi ethnic group (n=96; 56.1%), single (n=118; 69%), and lived with both parents (n=94; 55.0%). Over half (51.4%; n=88) of the participants reported high levels of anxiety, while two-thirds (n=141; 67.8%) exhibited high levels of depression. Variables such as academic level, receipt of financial bursary, and prior professional psychological support had a significant (p < 0.05) association with total GAD-7 and PHQ-9 scores. Correlation analysis revealed a strong positive correlation between total GAD-7 and PHQ-9 scores (r = 0.77, p < 0.001).Conclusion: Addressing the high levels of anxiety and depression among optometry students necessitates a comprehensive strategy that encompasses the augmentation of mental health resources, fostering resilience, and creating supportive environments. By implementing these strategies, educational institutions can enhance the mental health and well-being of optometry students, ultimately leading to improved academic outcomes and professional readiness.Keywords: anxiety, depression, mental health, optometry students